Hysteresis Phenomena in Biology - Noori, Hamid Reza.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The occurrence of hysteresis phenomena has been traditionally associated with mechanical and magnetic properties of materials. However, recent studies on the dynamics of biological processes suggest switch-like behavior that could be described by mathematical models of hysteresis. This book presents the milestones and perspectives of biological hysteresis and provides a comprehensive and application-oriented introduction to this subject. The target audience primarily comprises researchers but the book may also be beneficial for graduate students.
Introduction -- Bifurcation Theory and Bistability -- Preisach Models -- Examples of Hysteresis Phenomena in Biology.
Keywords: Mathematics; Functional analysis; Physiology -- Mathematics; Biomedical engineering; Mathematics; Physiological, Cellular and Medical Topics; Biomedical Engineering; Biophysics and Biological Physics; Mathematical and Computational Biology; Functional Analysis